Modifying Barium Hexaferrite Magnets by Adding Sol-Gel Synthesized Cobalt Ferrite Phase - Thanida Charoensuk; Wannisa Thongsamrit; Anuchit Hunyek; Komkrich Chokprasombat; Pongsakorn Jantaratana; Chitnarong Sirisathitkul (My University, 2023)
Combining various types of ferrites brings about magnetic properties desirable for different applications. This study aims to modify barium hexaferrite (BaFe12O19) by physically mixing it with cobalt ferrite (CoFe2O4). BaFe12O19/CoFe2O4 magnets were produced by ball-milling and pressing sol-gel-derived ferrite powders. The ferrite composites showed variations in magnetic properties from BaFe12O19 magnets with a saturation magnetization of 69.46 emu/g and a maximum energy product of 0.4529 MGOe. For the BaFe12O19:CoFe2O4 weight ratio of 4:1, both satura-tion and remanent magnetizations were increased due to the addition of CoFe2O4 with high magnetizations. However, the magnetizations were reduced when the BaFe12O19:CoFe2O4 ratio was reduced to 2:1. On the other hand, the coercivity was monotonously decreased with increasing CoFe2O4. Interestingly, the maximum energy product in this study was linearly decreased with the bulk density of the magnets from 3.59 to 3.15 g/cm3. It is concluded that magnetic properties could be modified from a facile physical mixing of ferrites.
Keywords: Barium ferrite; Cobalt Ferrite; Barium; Magnetic Properties and Synthesis of Ferrites